PERBANDINGAN EFISIENSI BIAYA PRODUKSI SEBELUM DAN SESUDAH PENERAPAN TOTAL QUALITY MANAGEMENT (TQM) PADA PT. PACIFIC INDO PACKING LAMONGAN - Rifai, M; Yulianto, Anton Eko (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2022)
Almost all industrial establishments have thought that increasing quality requires high production costs. But there is another opinion stating that the quality can lower costs if the company applies the correct management, including by implementing Total Quality Management (TQM). TQM is a way to improve performance on an ongoing basis at every level of operation or process using all human resources and capital available. Efficiency is the appropriateness ways to run something by not wasting time, effort and cost. The concept of TQM can bring a positive effect on improving the quality and cost savings. The production process is attention to quality will produce a product that is free from damage or failure, so the company will avoid waste or loss. This research was conducted at PT. Indo Pacific Packing Lamongan is located in the district of Lamongan Kembangbahu. The purpose of this study was to investigate the application of TQM in PT. Indo Pacific Packing and determine the cost effectiveness of production before and after implementation of TQM, by comparing the efficiency before and after the application of TQM. In conducting this research method used is a method of study on PT. Indo Pacific Packing Lamongan. From the results of this study showed that an increase in efficiency by 2.08% after the implementation of TQM and some activities are in accordance with the main elements of TQM. Thus the application of TQM in the company has been run well and have an influence on the efficiency of the production costs. Suggestions author of the company's successful implementation of TQM in the company should not make the management of PT. Indo Pacific Packing feel satisfied, and so maintained even increased further.